Antibody responses to an inactivated SARS-CoV-2 vaccine in individuals aged from 50 to 102 years - Zhu, Hong-Hong; Sun, Guo-Qing; Wu, Ji-Yu; Fan, Su-Qing; Zhu, Ying-Ying; Wang, Zhi-Cheng; Liao, Xiao-Fang (Frontiers in Immunology, 2023)
Objectives To assess antibody responses to an inactivated SARS-CoV-2 vaccine in individuals aged 50 and older. Methods We conducted a post-market cross-sectional seroepidemiology study. We recruited 4,632 vaccinated individuals aged 50 and older, measured their total serum SARS-CoV-2-specific antibody (TA), and collected correlates. The primary outcome was the geometric mean titer (GMT) of TA, and the secondary outcome was the decline of TA with age. Univariate, bivariate, and multivariate analyses were used to examine the associations of the TA GMT with age, and trend analyses were used to test whether their associations were significant. Results All participants had a detectable TA, which was generally at a low level across all age groups. The TA GMT (95% CI) in AU/mL was 3.05 (2.93, 3.18); the corresponding arithmetic mean (95% CI) was 17.77 (16.13, 19.42) in all participants and 4.33 (3.88, 4.84), 3.86 (3.49, 4.28), 3.24 (2.92, 3.59), 2.77 (2.60, 2.96), and 2.65 (2.48, 2.83) in the age groups of 50-54, 55-59, 60-64, 65-74, and 75 years or older, respectively. The TA GMT decreased with age with a Ptrend < 0.001. The TA GMT was significantly lower in those with hypertension or diabetes compared to those with neither. Conclusion The inactivated SARS-CoV-2 vaccine is effective in individuals aged 50 and older. This is the first study that has found an inverse dose-response relationship between ages and the low-level TAs. Older people, especially those with chronic diseases, should get the SARS-CoV-2 vaccine, and their vaccination frequency, dose, and method may need to be different from those of younger people.